Adipocyte-specific Beclin1 deletion impairs lipolysis and mitochondrial integrity in adipose tissue - Yeonho Son; Yoon Keun Cho; Abhirup Saha; Hyun-Jung Kwon; Ji-Hyun Park; Minsu Kim; Young-Suk Jung; Sang-Nam Kim; Cheoljun Choi; Je-Kyung Seong; Rayanne B. Burl; James G. Granneman; et al. (Molecular Metabolism, 2020)
Objective: Beclin1 is a core molecule of the macroautophagy machinery. Although dysregulation of macroautophagy is known to be involved in metabolic disorders, the function of Beclin1 in adipocyte metabolism has not been investigated. In the present study, we aimed to study the role of Beclin1 in lipolysis and mitochondrial homeostasis of adipocytes. Methods: Autophagic flux during lipolysis was examined in adipocytes cultured in vitro and in the adipose tissue of mice. Adipocyte-specific Beclin1 knockout (KO) mice were used to investigate the activities of Beclin1 in adipose tissues. Results: cAMP/PKA signaling increased the autophagic flux in adipocytes differentiated from C3H10T1/2 cells. In vivo autophagic flux was higher in the brown adipose tissue (BAT) than that in the white adipose tissue and was further increased by the β3 adrenergic receptor agonist CL316243. In addition, surgical denervation of BAT greatly reduced autophagic flux, indicating that sympathetic nerve activity is a major regulator of tissue autophagy. Adipocyte-specific KO of Beclin1 led to a hypertrophic enlargement of lipid droplets in BAT and impaired CL316243-induced lipolysis/lipid mobilization and energy expenditure. While short-term effects of Beclin1 deletion were characterized by an increase in mitochondrial proteins, long-term Beclin1 deletion led to severe disruption of autophagy, resulting in mitochondrial loss, and dramatically reduced the expression of genes involved in lipid metabolism. Consequently, adipose tissue underwent increased activation of cell death signaling pathways, macrophage recruitment, and inflammation, particularly in BAT. Conclusions: The present study demonstrates the critical roles of Beclin1 in the maintenance of lipid metabolism and mitochondrial homeostasis in adipose tissues.